Analysis of creatine labels by RDC nº 18/2010 sold in the city of Natal-RN - Brito de Araújo, Sarah Rachell (2015)
Introduction: Nutrition and hydration are essential for optimal performance and recovery of physical activity practitioners although supplementation sometimes become necessary. Creatine has several ergogenic effects but it is necessary that supplements present on their labels all information required by law. Aim: To analyze the labels of creatine supplements according to the law. Materials and Methods: 18 creatine labels of 17 different brands were evaluated using a proper check list according to RDC n ° 18/2010. Results: Of analyzed labels 77.8 % were irregular. Discussion: The inadequacies were: description of the product (5.5%), list of ingredients (5.5%), use of creatine monohydrate (22.2 %) and minimum degree of purity of 99.9 % (77.8 %). Besides, contradictions regarding the translation of the label and method of use with the recommendations of the ministry of health were detected. Conclusion: The irregularities of the labels with the illegal practice of many professionals can lead to errors in the consumption of supplements. Close monitoring isrequired in order to provide consumer safety, ensuring the effectiveness of the products.